Eating Attitudes and Life Habits of Institutionalized Elderly People in the Northeast Capital (Research, Society and Development, 2020)
The objective of this study was to know the eating attitudes and lifestyle habits of institutionalized elderly people. This is a descriptive cross-sectional research with a non-probabilistic sample, for convenience, composed of 19 elderly people residing in three LTCFs located in a capital of the Northeast. Data were obtained in the second half of 2017, using a semi-structured form composed of 25 questions. Descriptive statistics were used to present the results. Among those surveyed, there was a prevalence of women (68.5%) to the detriment of men (31.6%), the majority of whom were eighty years old or older (52.7%), in addition to hypertensive, diabetic and sedentary individuals. Regarding eating attitudes, 47% and 11%, respectively, were partially and totally dissatisfied with the food provided in the institutions; 69% had 5 to 6 meals / day; for 74% the quantity offered was sufficient; 36.8% reported aversion to some foods; everyone was in the habit of not adding salt to the ready meal and, also, they found the place comfortable for them. As for the preparations that brought more memories, there was a greater mention for salty foods; 63.2% pointed out that there were differences between the current diet and the past diet; 57.9% reported no restrictions on food intake for health reasons. Regarding the specificities of food consumption, there was an inadequacy in the fruit and vegetable groups for most elderly people; 48% ingested three to six glasses of water / day; 89.5% were not in the habit of exchanging the meal for a snack; for 58.0% and 63.2%, respectively, the consumption of industrialized soft drinks / juices; of cakes, cookies (sweets, stuffed) and other goodies occurred only at social gatherings or on special occasions. It was evidenced that this elderly population residing in these three institutions presented adjustments and inadequacies related to food consumption and the menus offered; singularities of food habits and sedentary lifestyle. Therefore, it requires adjustments to the usual menu and encouragement of social interaction activities aiming at a later change in eating habits and lifestyle.